Analisis Penerapan EYD Dalam Sebuah Karya Ilmiah - Mai Sri Lena; Sahrun Nisa; Rafina Suciwanisa; Latania Yusma Fitas Taftian (LPPM Politeknik Pratama, 2023)
This study aims to analyze the placement of Enhanced Spelling (EYD) in a scientific work. EYD is a guideline used to improve and perfect Indonesian spelling. Scientific work is a type of writing that has specificity in the style of writing and the use of appropriate language. In this research, we collect several scientific papers from various disciplines and analyze the use of EYD in them. The method used is literature study and content analysis. We identify and compare the use of EYD in the context of words, punctuation, and other grammatical rules. The results of the analysis show variations in the use of EYD in scientific work. Some scholarly works adhere strictly to the EYD rules, paying attention to every aspect of spelling and grammar. However, several scientific works also show violations or deviations from the EYD rules. In this study, we also identify factors that influence the placement of EYD in scientific work. These factors include the author's background, scientific discipline, and language usage habits. This research is expected to provide a better understanding of the use of EYD in scientific work and provide recommendations for increasing awareness and compliance with EYD rules. In conclusion, this study reveals variations in the placement of EYD in scientific work. The importance of understanding and applying EYD rules in scientific work is a major concern. Consistent and correct use of EYD will improve the quality and uniformity of scientific writing, and make it easier for readers to understand and evaluate scientific work.